Birth Brachial Plexus Palsy: An Indian Perspective - Thatte, Mukund R.; Shah, Harsh R.; Hiremath, Amita (Seminars in Plastic Surgery, 2023)
Birth brachial plexus palsy (BBPP) is an unfortunate outcome of a difficult labor, which can often lead to long-lasting upper limb impairments. Spontaneous recovery may or may not occur. Timely diagnosis of the condition and initiation of the appropriate treatment can be instrumental in decreasing the functional impact. The management begins right from the day the child presents first and ranges from physiotherapy to surgical intervention such as nerve repair/transfer or grafts. The sequelae of the condition are also quite common and need to be detected preemptively with initiation of appropriate treatment. However, prevention is the key to reducing the incidence of secondary deformities. In this study, the team of authors, based on their considerable experience, discuss their approach to the management of BBPP. This is done in the background of Indian cultural practices and social constraints. A detailed discussion has been done on importance of preoperative passive joint mobilization regime and role of botulinum toxin in the authors' preferred ways of surgical correction of primary as well as secondary deformities. An extensive review of peer-reviewed publications has been done in this study, including clinical papers, review articles, and systematic review of the subject. Good results are possible with early and appropriate intervention even in severe cases.
Keywords: birth brachial plexus palsy; co-contractions; Botox; brachial plexus surgery; brachial plexus secondary deformities